2006
DOI: 10.1016/j.micron.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The regenerative cells during the metamorphosis in the midgut of bees

Abstract: The midgut epithelium of bees is formed by the digestive cells, responsible for enzyme secretion and nutrient absorption and for small regenerative cells that are placed in nests scattered among the digestive cells. During metamorphosis, the larval midgut epithelium degenerates and a new adult midgut epithelium is built during larval differentiation of regenerative cells. The present work focuses on the midgut epithelial modifications during the post-embryonic development of the stingless bee Melipona quadrifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 24 publications
3
65
0
12
Order By: Relevance
“…164 During metamorphosis, the larval midgut epithelium degenerates and a new adult midgut epithelium is built during larval differentiation of regenerative cells. [165][166][167][168] PCD in honeybee larvae was found during normal larval development using scanning electron microscopy 169 and histochemical and immunohistochemical methods. 166 Acid phosphatase (AP) activity can be used as a marker of lytic activity in the cell.…”
Section: Pcd Of Nurse Cells and Follicle Cells Is Absolutely Requiredmentioning
confidence: 99%
“…164 During metamorphosis, the larval midgut epithelium degenerates and a new adult midgut epithelium is built during larval differentiation of regenerative cells. [165][166][167][168] PCD in honeybee larvae was found during normal larval development using scanning electron microscopy 169 and histochemical and immunohistochemical methods. 166 Acid phosphatase (AP) activity can be used as a marker of lytic activity in the cell.…”
Section: Pcd Of Nurse Cells and Follicle Cells Is Absolutely Requiredmentioning
confidence: 99%
“…These cells predominate along the S. frugiperda midgut epithelium and are considered responsible for the absorption of digested food, and demonstrate morphology similar to that of other Lepidoptera (8,21). Studies by Harper & Hopkins (22) and Harper & Granados (23), indicate that these epithelial cells are also responsible for secretion of a micro fiber net soaked in a matrix of proteins and glycoproteins -denominated a peritrophic membrane -which performs various functions such as: the protection of the epithelium against chemical and mechanical damage caused by the alimentation, the creation of a physical barrier against micro-organisms and digestion division (18). Pinto & Fiuza (24), analyzing the histology of the midgut of A. gemmatalis caterpillars with an optical microscope, observed that the alimentary canal is divided basically into three portions, which are: the anterior intestine or stomodeum, the middle intestine or mesentero, and the posterior intestine or proctodeus.…”
Section: Histology Of Lepidopteramentioning
confidence: 69%
“…The regenerative cells are undifferentiated and are responsible for the renovation of the midgut epithelium, substituting the cells that wear out and are lost during the digestive process -they also make it possible for the alimentary channel to grow larger at each ecdysis. They are found at the base of the midgut, alone or in groups, and there are no differences in their abundance along the midgut (16,17,18). Changes in the alimentary canal, especially in the region of the midgut, can affect the growth and development of insects, as well as all the physiological events, because these processes depend on adequate food, on its absorption and transformation in the alimentary canal (9,11).…”
Section: Histology Of Lepidopteramentioning
confidence: 99%
“…Midgut progenitor cells that differentiate into all types of the midgut epithelial cells have been described mainly for arthropods. They are described as cells which show the features of both midgut stem cells and digestive cells (Martins et al, 2005;Cruz et al, 2011;Chajec et al, 2012). The amount of reserve material (e.g.…”
Section: Discussionmentioning
confidence: 99%